TLR4-mediated Cox-2 expression increases intestinal ischemia/reperfusion-induced damage - Moses, Tiffany (The Society for Leukocyte Biology, 2009)
Mesenteric IR induces significant inflammation and immune-mediated mucosal damage. TLR4 is a critical receptor in the induction of the inflammatory response and plays a role in intestinal homeostasis. To determine the role of TLR4 in IR-induced epithelial damage, we performed IR studies using TLR4(lps-def) and TLR4(lps-n) mice and analyzed mucosal damage and inflammation. We found that the absence of TLR4 or TLR4-induced signaling attenuated local mucosal damage with significantly decreased cytokine and eicosanoid secretion including PGE2 production. Similar results were seen in MyD88−/− mice. Wild-type mice treated with NS-398 (a Cox-2 inhibitor) not only decreased PGE2 production but also attenuated tissue damage. In contrast, PGE2 was not sufficient to induce damage in the TLR4(lps-def) mice. Together, these data indicate that TLR4 stimulation of Cox-2 activation of PGE2 production is necessary but not sufficient for intestinal IR-induced damage and inflammation.